2017
DOI: 10.1590/1983-40632016v4745475
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemical properties and nutrients in maize fertilized with urban waste compost1

Abstract: Urban waste compost has a potential to be used as an organic fertilizer in agriculture, but field studies are required to define the recommendable rates for crops. This study aimed at evaluating the effect of fertilization with urban waste compost on the soil chemical properties, yield, nutrient and heavy metal contents, in maize leaves and grains. The field experiment was carried out in a randomized complete block design, with seven treatments and four replications. The treatments consisted of six urban waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Marathe et al (2017) showed that the uncontrolled discharge of untreated urban wastes can contribute to an overall increase in the abundance and diversity of antibiotic resistance genes (ARGs) in the environment. Mantovani et al (2017) aimed at evaluating the effect of fertilization with urban wastes compost on the soil chemical properties, yield, nutrient, and heavy metal contents. Brina et al (2018) focused on the placespecific governance structures and socio-technical experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Marathe et al (2017) showed that the uncontrolled discharge of untreated urban wastes can contribute to an overall increase in the abundance and diversity of antibiotic resistance genes (ARGs) in the environment. Mantovani et al (2017) aimed at evaluating the effect of fertilization with urban wastes compost on the soil chemical properties, yield, nutrient, and heavy metal contents. Brina et al (2018) focused on the placespecific governance structures and socio-technical experiments.…”
Section: Introductionmentioning
confidence: 99%